Corporate Governance Mechanisms and Sustainability Reporting of Listed Manufacturing Firms in Nigeria. (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examined corporate governance mechanisms and sustainability reporting practices of listed manufacturing firms in Nigeria. The study adopted a correlational and causal research design, the study analyzed secondary data from the annual financial statements and sustainability reports of 27 manufacturing firms listed on the Nigerian Exchange Group (NGX) over a fifteen-year period (2010–2024). Descriptive statistics were employed to summarize the characteristics of the variables, while Pearson correlation analysis was used to assess the strength and direction of associations among them. For inferential analysis, the system Generalized Method of Moments (GMM) estimator was applied to account for endogeneity, firm-specific effects and dynamic persistence. The study found that board director nationality has a significant positive effect on sustainability reporting, suggesting that internationally diverse boards enhance ESG disclosure practices. In contrast, board director reputational capital did not significantly influence sustainability reporting. The findings underscore the importance of diverse and internationally experienced boards in promoting transparency and accountability in sustainability reporting among manufacturing firms in Nigeria. This paper also contributes to existing knowledge in the field of sustainability reporting by looking at manufacturing firms in Nigeria. Based on these results, the study recommends that firms encourage board nationality diversity and establish structured ESG governance frameworks to enhance the quality and credibility of sustainability reporting.